Agenda setting in the world of online news: New questions for new environment - Ninković Slavnić, Danka N (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
The paper explores whether agenda setting theory is a fruitful approach to understand online news communication. To answer this question, the distinction between vertical and horizontal media is used and applied to online communication in order to establish their role in news circulation. Vertical media are defined as news media targeting the whole population, while horizontal media are those that enable horizontal flow of communication among different subjects, including citizens. The role these two types of media play in setting issue and attribute agenda is discussed. Additionally, their interconnection is considered in the context of constructing media agenda. Despite the fact that online communication flow is complex and goes in different directions, this paper marks horizontal media as a significant force in making community issue agenda and in interpreting attribute agenda set by vertical media. At the same time, vertical online news media are speculated to be still the major factor when it comes to public issue agenda, the agenda that is specific medium of connection for one society. This paper is trying to provide theoretical framework for thinking about agenda setting and to stimulate further empirical research that will shed additional light on the process.